The Relation Between Discipline Identity and Academic Achievement Within a Marketized Higher Education Context: A Serial Mediation Model of Approaches to Learning and Course Complaints - Taylor Bunce, Louise; Bennett, Melanie; Jones, Siân E. (Frontiers in Psychology, 2022)
Social-psychological dimensions of learning are under-researched, but they affect student achievement. Within a marketized higher education context in England, UK, this study examined whether the relation between students’ social identities as members of their discipline and academic achievement could be further understood by considering the mediating roles of approaches to learning and frequency of making course complaints. Undergraduates (N=679) completed a questionnaire to assess these constructs. As expected, approaches to learning and course complaining both acted as serial mediators of the link between discipline identification and academic achievement: stronger discipline identification was related to more deep approaches to learning, less complaining, and higher achievement, whereas weaker discipline identification was related to more surface approaches to learning, more complaining, and lower achievement. The findings suggest that addressing these social-psychological aspects of learning could improve students’ academic achievement.